Educating Phronesis and Phronesis for Educators: Two Neo-Aristotelian Perspectives - Popovska, Jasmina (Филозофски факултет, УКИМ, Скопје, 2022)
Aristotle in Nichomachean Ethics lays the foundation of the concept of intellectual virtues and of phronesis as a virtue crucial for attaining eudaimonia. However, Aristotle did not elaborate on detailed implications of phronesis considering education although this topic has wide theoretical potential. The neo-Aristotelian reflections on education, motivated mainly from the development of virtue ethics, shed new light on the educational potential of phronesis in two directions: first, directed towards moral education theory, and second, directed towards professional ethics in educational practices. This article will make brief overview of these two “reconstructivists” perspectives. Firstly, the discussion will be focused on their attempts for explaining the development of phronesis-guided virtue form habituated virtue and its educational implications. Secondly, the fundamentals of the role of phronesis in developing professional wisdom in the educational practice will be discussed. Lastly, the theoretical and practical successfulness of the two perspectives as well as their role in ethical education in contemporary classrooms will be elaborated on.
Keywords: education, phronesis, neo-aristoteliainism, virtue ethics